Folic acid alleviates the negative effects of dexamethasone induced stress on production performance in Hyline Brown laying hens - Xi Sun; Chaohui Wang; Sijing Li; Xiaoying Liu; Yun Li; Yumeng Wang; Yuxin Niu; Zhouzheng Ren; Xin Yang; Xiaojun Yang; Yanli Liu (Animal Nutrition)
Multiple stressors are believed to deteriorate production performance and cause substantial economic losses in commercial poultry farming. Folic acid (FA) is an antioxidant compound that can improve oocyte function and regulate gut microbiota composition. The current study was conducted to investigate the role of FA in alleviating stress and improving production performance. Sixty Hyline Brown laying hens at 21 weeks of age were randomly divided into three groups, with 10 replicates in each group and each replicate containing two chickens. Each group received basic diet and saline injection (Con group), basic diet with dexamethasone (DXM) injection (DXM group), or basic diet supplemented with FA (13 mg/kg in the premix) with DXM injection (FA group). The feeding trial lasted five weeks. Birds in the DXM and FA groups receiving subcutaneous DXM injections at a dosage of 4.50 mg/kg per day during the first seven days of the trial. Results showed that the levels of corticosterone, triglyceride, total cholesterol, and malondialdehyde in serum were significantly increased in the DXM group (P < 0.05), while the concentrations of FA and 5-methyltetrahydrofolate were decreased in the DXM group (P < 0.05). Laying hens in the DXM group had lower laying rates and egg quality, including egg weight, eggshell thickness, eggshell strength, albumen height, and Haugh units (P < 0.05). Conversely, FA alleviated these negative impacts. Through transcriptome analysis, a total of 247 and 151 differentially expressed genes were identified among the three groups, and 32 overlapped genes were further identified. Moreover, 44 and 59 differential metabolites were influenced by DXM and FA, respectively. Kyoto Encyclopedia of Genes and Genomes enrichment from the transcriptome and metabolomics showed that the reduced production performance may be due to the disturbance of oocyte production, calcium metabolism, and oxidative stress. Analysis of 16S rRNA gene amplicon sequences revealed the differential microbial composition and potential functional changes among the different groups. LEfSe analysis showed that Mucispirillum and Nautella were the predominant bacteria in the DXM group, while Clostridium was the predominant bacteria in the FA group. Functional prediction demonstrated that stressors enhanced fatty acid biosynthesis, while betaine biosynthesis and retinol metabolism were elevated in the FA group. Dietary FA reversed the elevated levels of bile acids (BA), including cholic acid, taurodeoxycholic acid, and taurochenodeoxycholic acid (P < 0.05). The DXM group showed an overall decrease in short-chain fatty acids (SCFA), but FA restored the concentrations of acetic acid, propionic acid, and isobutyric acid (P < 0.05). In conclusion, this study reveals that dietary FA can alleviate the degradation of production performance caused by stress through improving circulating antioxidant capacity, maintaining intestinal microbiota homeostasis, and regulating SCFA and BA biosynthesis. Thus, highlighting the prominent role of gut microbe-host interactions in alleviating multi-stresses.